The Correlation of Knowledge, Attitudes, and Family Support with Adolescent Sexual Behavior in Students of Public Senior High School Mutis Eban, West Miomaffo Subdistrict, Timor Tengah Utara District - Patricia Adhica Ahoinnai; Rina Waty Sirait; Indriati A. Tedju Hinga (Universitas Nusa Cendana, 2022)
Premarital sex often occurs in adolescence. This happens due to the lack of knowledge among teenagers and limited information delivered by parents about the impact of premarital sex. This study aimed to determine the knowledge, attitudes, and family support for adolescent sexual behavior in students of SMA Negeri Mutis Eban, West Miomaffo Subdistrict, North Central Timor District. The study used a cross-sectional design with a quantitative approach. This research was conducted at the Public Senior High School Mutis Eban in March-June 2021. The population in this study were all 10th and 11th-grade students totaling 326 people. The sample of 115 students was selected using the proportional random sampling technique. The data were analyzed with a 95% confidence level (α = 0.05). The results showed that knowledge (p-value= 0.000), attitudes (p-value= 0.000), and family support (p-value= 0.000) had a significant relationship to sexual behavior in students of SMA Negeri Mutis Eban. The school needs to collaborate with related sectors in increasing promotive and preventive reproductive health in adolescents.